Quercetin Attenuates Cardiac Hypertrophy by Inhibiting Mitochondrial Dysfunction Through SIRT3/PARP-1 Pathway - Chen, Wen-Jing; Cheng, Yan; Li, Wen; Dong, Xiao-Kang; Wei, Jian-liang; Yang, Chuan-Hua; Jiang, Yue-Hua (Frontiers in Pharmacology, 2021)
Cardiac hypertrophy is an important characteristic in the development of hypertensive heart disease. Mitochondrial dysfunction plays an important role in the pathology of cardiac hypertrophy. Recent studies have shown that sirtuin 3 (SIRT3)/poly (ADP-ribose) polymerase-1 (PARP-1) pathway modulation inhibits cardiac hypertrophy. Quercetin, a natural flavonol agent, has been reported to attenuate cardiac hypertrophy. However, the molecular mechanism is not completely elucidated. In this study, we aimed to explore the mechanism underlying the protective effect of quercetin on cardiac hypertrophy. Spontaneously hypertensive rats (SHRs) were treated with quercetin (20 mg/kg/d) for 8 weeks to evaluate the effects of quercetin on blood pressure and cardiac hypertrophy. Additionally, the mitochondrial protective effect of quercetin was assessed in H9c2 cells treated with Ang II. SHRs displayed aggravated cardiac hypertrophy and fibrosis, which were attenuated by quercetin treatment. Quercetin also improved cardiac function, reduced mitochondrial superoxide and protected mitochondrial structure in vivo. In vitro, Ang II increased the mRNA level of hypertrophic markers including atrial natriuretic factor (ANF) and β-myosin heavy chain (β-MHC), whereas quercetin ameliorated this hypertrophic response. Moreover, quercetin prevented mitochondrial function against Ang II induction. Importantly, mitochondrial protection and PARP-1 inhibition by quercetin were partly abolished after SIRT3 knockdown. Our results suggested that quercetin protected mitochondrial function by modulating SIRT3/PARP-1 pathway, contributing to the inhibition of cardiac hypertrophy.